Red Hot Steel: Challenges of 3D Optical Metrology in Open-Die Forging - M. Tarabini (The International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences)
Complex challenges arise from the integration of 3D optical metrology in contemporary steelmaking and metal-working operations. Contrary to expectation, the greatest difficulties do not arise from the obstacles posed by high temperatures or harsh environments requiring robust measurement solutions. Often, there's a nuanced understanding of metrology concepts, with experts struggling to distinguish between instrumental uncertainty, measurand variability and definitional uncertainty. This paper aims to underscore the importance of technological innovation and interdisciplinary collaboration in efficiently adopting 3D optical measurement systems in modern metalworking industries. A case study focused on a 2D profilometer is presented and discussed.